(untitled) (Global Journal of Human-Social Science, 2023)
The Computer Age also known as Digital Age and Information Age and New Media Age has been the most impactable historical period of human civilization If well the truth that its precursor the Industrial Revolution drastically changed the way societies lived and worked and plaid the magnitude of its impact in terms of communication cannot be compared with the one the Computer Age has brought into today s society Consequently technology and human interaction have become a modern society norm Indeed a well-considered focus for academic and scientific research The study takes on the Communication philosophy and Communication Theory to present an outlook on searching for information through technology and human interaction It focuses on the Shamon Weaver Model to transcribe this model communication concept into a Search Engine Communication Model SECM The study has used a qualitative method approach for the collection and analysis of correlated materials such as books and publications and Internet-accredited websites The results of this study are beneficial to the academic and scientific communities respectively